Философский концепт "души" как устремленность к благу - Фидровская, Мария Георгиевна (НТУ "ХПИ", 2017)
В этой статье представлено гипотеза на тему того, что такое душа. Развитие науки дало возможность философии исходить из достоверных источников и экспериментов, в то же время не отрицая философию, но давая ей материал для рассмотрения. Также следует заметить, что мы представляем религиозную позицию и именно с этой позиции в основном рассматриваем душу.

In this article it is being proposed a hypothesis on the subject of what soul is. The genesis of the science gave an opportunity to the philosophy to outcome of verified sources and experiments, at the same time not denying philosophy but giving it the material for consideration. Also it should be noted, that we are of the religious position and particularly of this position we are mostly considering the soul. We are considering soul as a fundamental process of beautiful and ugly both itself and what it is percepting. Our concept has been supported by the opening in science about amoeba that instead of its simplicity still has a position on pleasant and unpleasant.
Philosophical concept of "the soul" as a turning to the good
Keywords: амеба; психология; творение; эстетика; amoeba; psychology; creation